1982
DOI: 10.1161/01.cir.65.5.936
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that hospital care for acute myocardial infarction has not contributed to the decline in coronary mortality between 1973-1974 and 1978-1979.

Abstract: SUMMARY To investigate whether the reported 17% decline in the national rates of acute ischemic heart disease mortality between 1973 and-1978 was attributable to decreased in-hospital mortality for patients with acute myocardial infarction (MI), we surveyed all 63 acute care.hospitals in the Boston, Massachusetts, area.Compared with 1973-1974, more [1978][1979] MI patients were admitted to hospitals in metropolitan Boston, and especially to the five university teaching hospitals. Between 1973Between -1974Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(9 citation statements)
references
References 25 publications
(2 reference statements)
0
9
0
Order By: Relevance
“…Nonetheless, studies carried out in male employees of the DuPont Company suffering AM123 and in patients hospitalized with AMI in metropolitan Baltimore, Md.,31 Minneapolis-St. Paul, Minn.,22 Rochester, Minn.,32 and in the Pee Dee area of South Carolina20 show an improvement over time in in-hospital survival after AMI, with the sole exception to these trends being the study of nonvalidated cases of AMI admitted to greater Boston hospitals. 33 Temporal declines in in-hospital case-fatality rates after AMI for men and women have also been seen in data compiled from the National Hospital Discharge Survey. 34 Although the results of the present study are in agreement with most studies that have examined temporal trends in in-hospital survival after AMI, increases in in-hospital mortality were nonetheless observed during the most recent two periods under study among men and women, and no clear trends in short-term mortality were seen in the two sexes over the periods under study.…”
Section: Discussionmentioning
confidence: 86%
“…Nonetheless, studies carried out in male employees of the DuPont Company suffering AM123 and in patients hospitalized with AMI in metropolitan Baltimore, Md.,31 Minneapolis-St. Paul, Minn.,22 Rochester, Minn.,32 and in the Pee Dee area of South Carolina20 show an improvement over time in in-hospital survival after AMI, with the sole exception to these trends being the study of nonvalidated cases of AMI admitted to greater Boston hospitals. 33 Temporal declines in in-hospital case-fatality rates after AMI for men and women have also been seen in data compiled from the National Hospital Discharge Survey. 34 Although the results of the present study are in agreement with most studies that have examined temporal trends in in-hospital survival after AMI, increases in in-hospital mortality were nonetheless observed during the most recent two periods under study among men and women, and no clear trends in short-term mortality were seen in the two sexes over the periods under study.…”
Section: Discussionmentioning
confidence: 86%
“…Acute MI has distinct, generally approved diagnostic criteria used throughout the country, which might enhance the accuracy of discharge data. The even standard of hospital services and the regular admittance of MI Heleiin Gylling 30 25 20 15 10 patients to hospital make the discharge data useful in epidemiological research. The incidence figures in our study were somewhat lower than the results of CHD registries with an incidence of 5 3 1 000 for men and 1.91 000 for women in 1973'a2.…”
Section: Discussionmentioning
confidence: 99%
“…A selected group of surveillance studies of hospitalized AMI is shown in Table 2 [53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]. Time trends, by decade, for case fatality in those hospitalized, have consistently improved.…”
Section: Case Fatality In Hospitalized Amimentioning
confidence: 99%